Effect of Motivation and Work Environment on Employee Performance of PT. XYZ - Wenna Junianta Turnip (Institute of Computer Science (IOCS), 2020)
This study aims to determine the effect of motivation and work environment on employee performance.This research is a quantitative study with an associative method. The analysis method uses the questionnaire method. The population in this study were employees of PT. XYZ , amounting to 55 people. The statistical tests used are the classic assumption test, hypothesis testing, multiple linear regression analysis, correlation coefficients and the coefficient of determination.The results of this study indicate that the independent variables, namely Motivation (X1) and Work Environment (X2), have a positive and significant effect on the Performance of Employees of PT. XYZ .